2021
DOI: 10.1186/s12933-021-01332-4
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-glucose index is associated with in-stent restenosis in patients with acute coronary syndrome after percutaneous coronary intervention with drug-eluting stents

Abstract: Background The triglyceride-glucose (TyG) index is an alternative marker of insulin resistance (IR) and is closely associated with the prevalence and prognosis of atherosclerotic cardiovascular disease (ASCVD). However, the association between the TyG index and in-stent restenosis (ISR) after drug-eluting stent (DES) implantation in patients with acute coronary syndrome (ACS) remains unknown. Methods The present study retrospectively recruited pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 48 publications
(71 reference statements)
4
85
2
Order By: Relevance
“…Second, regarding the predictive power of the TyG index in CVD, especially in CAD, accumulating studies have shown that the predictive value of the TyG index for CAD is mild to moderate, suggesting that it is difficult to predict severe CVEs based on the TyG index alone. Nevertheless, Wang et al and Zhu et al demonstrated that when introducing the TyG index into an established risk model, TyG could significantly improve the predictive accuracy for MACEs in patients with ACS [ 32 , 39 ]. Thus, routinely adding the TyG index into clinical diagnostic models might help to refine cardiovascular risk stratification and enable the administration of more targeted therapeutics or prevention measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, regarding the predictive power of the TyG index in CVD, especially in CAD, accumulating studies have shown that the predictive value of the TyG index for CAD is mild to moderate, suggesting that it is difficult to predict severe CVEs based on the TyG index alone. Nevertheless, Wang et al and Zhu et al demonstrated that when introducing the TyG index into an established risk model, TyG could significantly improve the predictive accuracy for MACEs in patients with ACS [ 32 , 39 ]. Thus, routinely adding the TyG index into clinical diagnostic models might help to refine cardiovascular risk stratification and enable the administration of more targeted therapeutics or prevention measures.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al retrospectively recruited 1574 patients who were admitted for ACS and underwent successful drug-eluting stent (DES)-based PCI. They found that an elevated TyG index was independently and positively associated with the occurrence of DES-ISR [ 39 ]. However, the incremental predictive value of the TyG index for DES-ISR was slight; thus, multicentre, large-scale clinical studies are necessary to clarify the relationship between the TyG index and ISR.…”
Section: Tyg Index In Cardiovascular Diseases (Fig 2 ...mentioning
confidence: 99%
“…Moreover, substantial changes in the TyG index were positively correlated with CVD risk observed in the 62,443 participants without CVD at baseline in China [ 35 ]. In addition, in patients who underwent percutaneous coronary intervention (PCI) after acute coronary syndrome, an elevated TyG index was independently related to in-stent restenosis after drug-eluting stent implantation in the 62,443 general population in China with some predictive value [ 36 ]. The TyG index was significantly associated with future CVD risk in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-sectional observational studies among the Chinese and Korean populations illustrated that the TyG index was linked to arterial stiffness ( 49 , 50 ). Moreover, an elevated TyG index was positively correlated with in-stent restenosis in patients after drug-eluting stent ( 51 ). These data supported that a high TyG index was closely related to accelerated progression of CAD, cumulatively leading to a high risk of revascularization.…”
Section: Discussionmentioning
confidence: 99%